Examining the impact of organizational and individual characteristics on forensic scientists’ job stress and satisfaction - Holt, Thomas J. (Journal of crime and justice, 2017)
Research on job stress and satisfaction among police and correctional officers has dramatically improved our knowledge of the experiences of criminal justice system employees. There is, however, minimal research on the experiences of individuals whose work directly informs criminal justice practice, most notably forensic scientists who collect and analyze evidence in support of criminal investigations. This study is one of the first to address the gap in our knowledge using survey responses collected from a sample of 670 forensic scientists operating in local and state laboratories in 25 states across the US. Regression models demonstrate that scientists who report higher stress were females who worked more hours, who had a poor relationship with court actors, minimal managerial support, and role ambiguities that made it difficult to do their jobs. Those with greater job satisfaction were unmarried, highly educated individuals with positive attitudes toward their work, greater managerial support, and few problems concerning their roles in the workplace.